Pemberdayaan Perempuan Pengrajin Kebaya Melalui Pengembangan Kapasitas Produksi Dan Inovasi Desain Berbasis Kultural - Putu Setyarini; Lilis Yuningsih; I Wayan Gede Lamopia (Insan Kreasi Media, 2026)
This community service activity aims to enhance production capacity and strengthen the business identity of Putri Tailor Kebaya as a small-scale enterprise in the kebaya garment sector in Denpasar City, Bali. Managed by a female artisan, this business has significant potential due to the high demand for kebaya for traditional, religious, and formal events. However, the partner still faces several challenges, such as limited production equipment, the absence of a business brand identity, and a marketing system that remains relatively simple. This community service program employs the Participatory Action Research (PAR) method, consisting of several stages: identifying the partner’s problems, providing production equipment in the form of a Typical GC628-1 sewing machine, designing product packaging as a branding medium, and conducting product documentation to support business promotion. The results show that the addition of a sewing machine has improved production efficiency and accelerated order completion. Furthermore, packaging design with a clear brand identity has enhanced the business’s professional image and strengthened the competitiveness of kebaya products in the local market